Zero Point Plaque - Ghosh, Ayan (2023)
Plaque commemorating the 'Zero point' which was located at the St Thomas Cathedral, Churchgate. In the past, distances of all major roads were counted from this point, and milestones were placed in different parts of Mumbai (shown on the map). Of the 16 original milestones, 10 have been found at their original locations.